Rozmyślania sandomierskie Kaspra Drużbickiego na tle tradycji platońskiej i neoplatońskiej - Krenz, Joanna (Poznańskie Studia Teologiczne, 2011)
The article analyzes Rozmyślania sandomierskie (Sandomierz Meditations) by Kasper Drużbicki, a 17th century Jesuit. The text, which was probably read out during a monastic retreat, borders on homiletics and mystical writing. The author of the present article interprets it through the prism of strongly marked elements of Platonic and Neoplatonic tradition and tries to reconstruct the spiritual, philosophical and linguistic phenomena occurring at the interface of the physical and metaphysical spheres, among others the way symbols function, the shaping of the semantics of words, instability of the category of time, mutual permeation and complementation of the fields of esthetics and anesthetics. There are numerous references to philosophical writings and contemporary contexts within the theory of literature but their purpose is not so much to bring out factographical or historical dependencies or the existence of conscious intertextual references but rather to provide a detailed and multifaceted depiction of the main themes of Drużbicki’s work also in an attempt to elicit on these grounds certain general regularities in the history of human thought and religion.